2017
DOI: 10.1002/brb3.742
|View full text |Cite
|
Sign up to set email alerts
|

The impact of multiple sclerosis onset symptom on cardiac repolarization

Abstract: IntroductionMultiple sclerosis is associated with prolonged cardiac repolarization but the underlying physiology has remained unknown. In this study, we compared cardiac repolarization during the relapsing‐remitting multiple sclerosis (RRMS) disease course in patients with motor and sensory onset symptom.MethodsTwenty‐five RRMS patients with motor and 33 RRMS patients with sensory onset symptom having 12‐lead electrocardiogram (ECG) recorded at the time of the first demyelinating event (ECG1) as well as at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Two retrospective studies explored cardiac repolarisation, assessed as HR corrected QT intervals, in relation to aspects of MS. In one study of 58 RRMS patients, cardiac repolarisation was prolonged and HR increased during the disease course in patients with motor but not with sensory onset symptoms [83]. The other study, in 43 RRMS patients, found that deterioration of cardiac autonomic regulation during the disease course was associated with disabling but not with benign RRMS [84].…”
Section: Association With Ms Type and Disease Characteristicsmentioning
confidence: 99%
“…Two retrospective studies explored cardiac repolarisation, assessed as HR corrected QT intervals, in relation to aspects of MS. In one study of 58 RRMS patients, cardiac repolarisation was prolonged and HR increased during the disease course in patients with motor but not with sensory onset symptoms [83]. The other study, in 43 RRMS patients, found that deterioration of cardiac autonomic regulation during the disease course was associated with disabling but not with benign RRMS [84].…”
Section: Association With Ms Type and Disease Characteristicsmentioning
confidence: 99%